Improving students achievement in science subject by Using audio visual media in fifth grade elementary School student at 25 bukit kecil iv jurai Pesisir selatan - Yuni Frita (Fakultas Sastra Universitas Ekasakti, 2017)
Based on observations of researchers in primary schools 25 Small Hill District IV Jurai student learning outcomes is still low, and the learning undertaken by teachers still use conventional methods.This resulted in low student grades, namely the achievement of the average value of MID students is 65.26, while the KKM specified school is 70. To the authors through this study tried to improve student learning outcomes on science subjects. The purpose of this study was to describe the planning, implementation and improvement of learning outcomes. This type of research is classroom action research (class action research), this study used aqualitative approach. Learning to use that to make use of audio-visual media n. Learning Implementation Plan (RPP) is prepared by following the steps using audio-visual media to create a fun learning activity that can improve learning outcomes in grade V IPA. While the students were taken as the subject of research are all fifth grade students of SD Negeri 25 Small Hill District IV Jurai. The research data was obtained using tests and observation. The results of the physical LUs any increase student learning, the test cycle I average student learning outcomes is 72.15 increased in the second cycle to 82, 14. Additionally the activity of teacher and student activity also increased in each of a meeting n monitored through observation sheets by using audio-visual media to improve science learning outcomes in grade elementary school consisting of teachers and students aspects. The author takes the conclusions in this study that by learning to use the audio-visual media to improve learning outcomes IPA in Class V SD Negeri 25 Small Hill District IV Jurai